PENGARUH INDEKS BURSA DUNIA PADA INDEKS HARGA SAHAM GABUNGAN BURSA EFEK INDONESIA - I Wayan Agus Budi, Utama; Luh Gede Sri, Artini (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
The purpose of this study is to determine the effect of Dow Jones, Nikkei 225, FTSE 100 and Straits  Times Indexes on the Jakarta Composite Index (JCI) on September 2008 until December 2013. This study used non-participant observation method and the whole population was used as sample. The data was analized by multiple linear regression technique. The findings show that Dow Jones Index and Straits Times Index has a positif effect on JCI partially, meanwhile the FTSE 100 index and Nikkei 225 index do not affect JCI during September 2008 until December 2009.
Keywords: Jakarta Composite Index, Dow Jones Index, FTSE100 Index, Nikkei225 Index